2020
DOI: 10.3389/fmicb.2020.00116
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses by Human Macrophages to Infection With Mycobacterium tuberculosis and Non-tuberculous Mycobacteria

Abstract: Mycobacterium tuberculosis (MTB) and non-tuberculous mycobacteria (NTM) are formidable causes of lung diseases throughout the world. While MTB is considered to be more virulent than NTM, host factors also play a key role in disease development.To elucidate whether there are differential immune responses to various mycobacteria, THP-1 macrophages were temporally infected with MTB H37Rv or with four different NTM species. We found that cells infected with MTB had greater bacterial burden and p65 nuclear factor-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
(56 reference statements)
1
29
0
Order By: Relevance
“…Previous studies indicated that M. smegmatis strain induces IL-1β secretion. [34][35][36] Our results showed that the recombinant M. smegmatis strain expressing PPE13 (named as Ms_PPE13) enhanced cell death and IL-1β secretion in J774A.1, BMDMs, and THP-1 cells. PPE13 induces the transcription of pro-IL-β, raising the possibility that increased IL-1β protein may be due to increased transcription.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies indicated that M. smegmatis strain induces IL-1β secretion. [34][35][36] Our results showed that the recombinant M. smegmatis strain expressing PPE13 (named as Ms_PPE13) enhanced cell death and IL-1β secretion in J774A.1, BMDMs, and THP-1 cells. PPE13 induces the transcription of pro-IL-β, raising the possibility that increased IL-1β protein may be due to increased transcription.…”
Section: Discussionmentioning
confidence: 75%
“…Studies believed that patients have various physiological and biochemical responses to NTM infections and MTB. Feng et al [ 33 ] made a study on macrophages and believed that the activation of NF-κB in MTB patients was more significant in comparison with that in patients with NTM infections, and there were differences in IL-8, IL-10 and TNF-α in different infections. Additionally, Nurlela et al [ 34 ] also discovered that level of TNF-α in pleural fluid of patients with NTM infections and MTB was different, with that in MTB sufferers significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…The culturing of Mtb raises several issues, mainly relating to the growth rate of Mtb, which is substantially slower than other pathogenic organisms, most probably due to a selective pressure at which faster growing Mycobacterium spp. induces a greater immune response [27]. It can often take more than four weeks for Mtb to produce colonies using traditional Lowenstein-Jensen medium (LJ) [28].…”
Section: Direct Culture and Observationmentioning
confidence: 99%